Benefits associated with the standing position during visual search tasks - Bonnet, Cédrick T. (2023)
The literature on postural control highlights that task performance should be worse in challenging dual tasks than in a single task, because the brain has limited attentional resources. Instead, in the context of visual tasks, we assumed that (i) performance in a visual search task should be better when standing than when sitting and (ii) when standing, postural control should be better when searching than performing the control task. 32 and 16 young adults participated in studies 1 and 2, respectively. They performed three visual tasks (searching to locate targets, free-viewing and fixating a stationary cross) displayed in small images (visual angle: 22°) either when standing or when sitting. Task performance, eye, head, upper back, lower back and center of pressure displacements were recorded. In both studies, task performance in searching was as good (and clearly not worse) when standing as when sitting. Sway magnitude was smaller during the search task (vs. other tasks) when standing but not when sitting. Hence, only when standing, postural control was adapted to perform the challenging search task. When exploring images, and especially so in the search task, participants rotated their head instead of their eyes as if they used an eye-centered strategy. Remarkably in Study 2, head rotation was greater when sitting than when standing. Overall, we consider that variability in postural control was not detrimental but instead useful to facilitate visual task performance. When sitting, this variability may be lacking, thus requiring compensatory movements.